Intervensi Latihan Fisik Untuk Mengatasi Fatigue Pada Pasien Hemodialisis : Literatur Review - Fera Yosefina Pattikawa; Rosyidah - Arafat; Rini - Rachmawaty (Jurnal Keperawatan Muhammadiyah, 2020)
Background Fatigue is the most common symptom experienced by patients with Chronic Kidney Failure (CRF) and is subjective with a prevalence of 84% in CRF patients who have performed hemodialysis (HD). Fatigue can be overcome by 62.3% through physical exercise. Purpose of writing this review literature is to find out the appropriate physical exercise intervention in hemodialysis patients in overcoming fatigue. Methods used in collecting this article are using the Pubmed, Wiley, Google Scholar database with limitations on the publication of articles in 2009-2019, with relevant keywords. Results obtained are nine randomized controlled trial research articles that fit the inclusion criteria. The research article states that physical exercise interventions are intradialitic foot exercises, VREP exercises and range of motion exercises. The physical exercise intervention proves it can reduce fatigue complaints. Conclusion physical exercise can reduce complaints of fatigue, types of intradialytic leg exercises, VREP exercises and effective and efficient range of motion exercises for patients undergoing hemodialysis.